Warisan Plato bagi Santri: Transmisi Filsafat Yunani Kuno dan Implikasinya untuk Pendidikan Kontemporer (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
This study traces the historical and intellectual processes that enabled Plato's ideas to enter the tradition of Islamic philosophy and subsequently influence Islamic boarding school education in Indonesia. Starting from the increasing openness of Islamic boarding schools to classical humanities, this study aims to understand how Plato's ideas were transferred from the context of Ancient Greece, reinterpreted by Muslim philosophers, and integrated into traditional learning practices. Using a library-based qualitative approach with hermeneutic, historical-intellectual, and thematic methods, this study analyzes the transmission pathways that include the Abbasid translation movement, the interpretive contributions of figures such as Al-Kindi, Al-Farabi, and Ibn Sina, and the absorption of concepts through literature on ethics, logic, and adab. The findings show that Islamic boarding schools did not inherit Plato's ideas directly, but rather through the Islamic philosophical tradition that reshaped Platonic elements to fit the Islamic intellectual framework. Concepts related to spiritual education, character building, and ethical rationality are in line with the orientation of tazkiyah al-nafs, which is the foundation of Islamic boarding school pedagogy. This study confirms that the relationship between Plato's ideas and Islamic education emerged through a long creative process, not merely a transfer of texts. Practically, these findings highlight opportunities to develop a more reflective, critical, and virtue-centered pesantren curriculum, while encouraging further ethnographic research to explore how the classical philosophical heritage is reinterpreted in contemporary santri learning practices.